Development of Four-Tier Instrument at First Intermediate Level Chemistry Concepts - Wijayadi, Andri Wahyu; Fitriyah, Lina Arifah; Manasikana, Oktaffi Arinna (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2023)
Chemical concepts are tiered from simple to complex. If misconceptions occur in simple concepts, they can cause misconceptions in complex concepts. The four-tier instrument is a tool for detecting misconceptions. This research aims to develop and describe the validity and reliability of a four-tier instrument on junior secondary-level chemistry concepts. This development research consists of 6 procedures: (1) concept mapping, (2) testing, (3) defining unscientific concepts, (4) developing four-tier instrument prototypes, (5) validating four-tier instrument prototypes, and (6) finalization of four-tier instruments. The developed four-tier instrument consists of 27 questions that measure chemistry concepts at the junior intermediate level. The instrument received an expert validation score of 92.81% with very valid criteria. The test results on 30 samples showed a reliability value based on a Cronbach alpha score of 0.713 with good criteria. The four-tier instrument on lower secondary level chemistry concepts meets the validity and reliability requirements so that it can be used to diagnose misconceptions on lower secondary level chemistry concepts.